MODELING OF UNIVERSITY BUDGET ITEMS BY THE ACADEMIC PERFORMANCE DATA - Valery Y. Vilisov (Открытое образование (Москва))
Two processes of the university are modeled – teaching students, which are indicators of performance characteristics, and the process of harmonization of control figures of the budget for the next fi scal year. The first of them is presented with regression equations, the second – a model of consumer choice. Both models are interlinked and that allowed the scholarship fund to evaluate in terms of performance.